1973
DOI: 10.1111/j.1423-0410.1973.tb04365.x
|View full text |Cite
|
Sign up to set email alerts
|

An Inherited Blood Group A Variant in the Finnish Population

Abstract: Abstract. A variant of blood group A, provisionally designated Ainn, that occurs in an overall frequency of approximately 1 in 6,000 in Finnish blood donors is described. Agglutination involving a very small number of erythrocytes was observable only microscopically, even with the most powerful immune anti‐A sera. However, potent anti‐A antibody eluates were produced from cells sensitized with both natural and immune anti‐A or anti‐A + B sera. Anti‐A1 agglutinins were demonstrated in the sera of all cases, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In a recent article, Mohn et al [8] reported an incidence of approximately 1:6,000 for an atypical A variant described as 'A-finn'. No study giving the incidence of weak B variants is available in the literature.…”
Section: Contentsmentioning
confidence: 99%
“…In a recent article, Mohn et al [8] reported an incidence of approximately 1:6,000 for an atypical A variant described as 'A-finn'. No study giving the incidence of weak B variants is available in the literature.…”
Section: Contentsmentioning
confidence: 99%
“…The Finnish variant, tentatively called Afmn, has several character istics which make it possible to distinguish the phenotype from other known variants of A. The serological properties of the red cells, serum, and saliva have been described elsewhere [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…After being read macroscopically, the tubes with their contents were re-centrifuged, the cells gently dislodged, and all of the negative reactions viewed microscopically [10]. At least ten fields were examined at low power magnification (x 100), agglutinates counted and the average num ber per field calculated, as shown in table I.…”
mentioning
confidence: 99%